Study of $Υ$ production and cold nuclear matter effects in pPb collisions at $\sqrt{s_{NN}}=5~TeV$ - collaboration, L; Aaij, R; Adeva, B; Adinolfi, M; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Ali, S; Alkhazov, G; Cartelle, P; et al. (Springer Verlag, 2014)
Production of $Υ$ mesons in proton-lead collisions at a nucleon-nucleon centre-of-mass energy $\sqrt{s_{NN}}=5 TeV$ is studied with the LHCb detector. The analysis is based on a data sample corresponding to an integrated luminosity of $1.6 nb^{-1}$. The $Υ$ mesons of transverse momenta up to $15 GeV/c$ are reconstructed in the dimuon decay mode. The rapidity coverage in the centre-of-mass system is $1.5